Kebhinekaan dan Keberagaman : Integrasi Agama Ditengah Pluralitas - Francisca, Lidea; Diarsi, Shifa; Asrini, Vivi Indri; Handrajati, M. Rizki; Adenan, Ahmad (ALSYS, 2022)
This study intends to convey the issue of religious integration in the midst of plurality. Integration is mixing until it becomes a unity. Integration in many scientific fields is roughly defined as a form of unifying elements that are out of sync with their character and classification according to concepts, frameworks, and units. Integration is a concept that is applied in many fields, from social, political, cultural, to economic. In this study, the author uses the Library Research method, which is to collect data or scientific papers that aim at the object of research. Plurality means understanding diversity in order to be able to live tolerantly in the midst of the people. The people here are people who are diverse both culturally, religiously, linguistically, politically. Including ethnicity, culture, tradition, language, to the diversity that is Indonesia's diversity, religion often causes problems caused by the disparity with various factors that surround it. Therefore, a progressive step is needed to deal with diversity news which can explode at any time and cause huge losses.